Biological control of Parthenium hysterophorus using plant pathogen - Hasnan, Mohd Ridzuan (2016)
Parthenium hysterophorus is one of the serious weed that occupy in the agriculture and abandoned area in Asia including Malaysia. This weed caused several environmental hazardous and effect to human and livestock health. This weed potentially cause damage early as in the rosette stage which cause mouth ulcer to livestock after consuming it. Herbicides are frequently used to control this weed. However, the chemical residues may harm to human health, environment pollution, and causing the weed to develop resistance toward the active ingredient. Six plants pathogenic fungus and bacteria were screened for their potential to cause infections against Parthenium hysterophorus. Three bacteria isolate namely B1, B2 and B3. Fungus isolate namely A2, A4 and A5 were isolated from the infection Parthenium part. Based on the pathogenicity test, all the bacteria and fungus isolate screened cause infection and symptom to detached leaf of Parthenium hysterophorus and their ability to cause severe infection depended on the isolate of the pathogen. The level of damaged caused between fungi A2, A4 and A5 was significantly no different between the isolates as it develop averaged lesion size measured 6.2cm, 6.0cm and 6.4cm² after six days of incubation. All bacteria isolates produced infection symptom as indicates from the lesion size developed, with the (AUDPC) values of 16.68cm² (B1), 12.65cm² (B2) and 5.63cm² (B3). The rate of symptoms expension was significantly faster in B1 compared to B2 and B3, with the expansion rate of 1.08 cm/ day compared to 0.90cm/day and 0.48 cm/day for B1 and B3 respectively, From both isolated pathogen, it showed that B1 and A5 are more effective in causing infection symptom to the detach Parthenium leaf.